2021
DOI: 10.1111/1467-8268.12576
|View full text |Cite
|
Sign up to set email alerts
|

Breaking the carbon curse: The role of financial development in facilitating low‐carbon and sustainable development in Algeria

Abstract: This paper investigates the oil resource abundance and environmental quality nexus in Algeria, with emphasis on the role of oil export receipts and domestic oil consumption, and whether financial development is a policy option for reducing carbon dioxide (CO2) emissions in the economy. Using time series data from 1971 to 2016, the Bayer–Hanck test for cointegration confirms the presence of a long‐run equilibrium relationship among the variables. Further analyses based on the auto‐regressive distributed lag (AR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 51 publications
1
9
0
Order By: Relevance
“…Further, a growing body of literature has confirmed an intrinsic link between CO 2 emission and economic expansion (Abdulrazaq, 2020Aboagye, 2017Arouri et al, 2014;Balsalobre-Lorente et al, 2018;Ike et al, 2020;Iorember et al, 2020;Musa et al, 2021;Nwani et al, 2021;Odhiambo, 2015Odhiambo, , 2017Shahbaz et al, 2020;Usman, Alola, et al, 2020;. However, findings of their exact relationship still differ and remain a contentious issue.…”
Section: Income and Environmental Degradationmentioning
confidence: 99%
“…Further, a growing body of literature has confirmed an intrinsic link between CO 2 emission and economic expansion (Abdulrazaq, 2020Aboagye, 2017Arouri et al, 2014;Balsalobre-Lorente et al, 2018;Ike et al, 2020;Iorember et al, 2020;Musa et al, 2021;Nwani et al, 2021;Odhiambo, 2015Odhiambo, , 2017Shahbaz et al, 2020;Usman, Alola, et al, 2020;. However, findings of their exact relationship still differ and remain a contentious issue.…”
Section: Income and Environmental Degradationmentioning
confidence: 99%
“…The paper's contribution is in threefolds: In the first place while research has indicated the need to reduce carbon dioxide emissions (Kwakwa and Adusah-Poku, 2020;Nwani et al, 2021; Natural resources, debt and carbon emissions Adebayo and Rjoub, 2021;Chien et al, 2021) empirical studies on the issue for Ghana is limited when compared to other developing countries. The study therefore helps to provide additional knowledge on the carbon dioxide emissions literature on the Ghanaian economy.…”
Section: Introductionmentioning
confidence: 99%
“…The paper's contribution is in threefolds: In the first place while research has indicated the need to reduce carbon dioxide emissions (Kwakwa and Adusah-Poku, 2020; Nwani et al. , 2021; Adebayo and Rjoub, 2021; Chien et al.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, attention is gradually starting to rise on the subject matter for the case of African countries. However, this attempt has only been well-documented in a few studies (Ben Jebli et al 2015 ; Iorember et al 2020 , 2021 ; Nwani et al 2021 ). Ben Jebli et al ( 2015 ) explored the causality links between growth, renewable energy consumption, and carbon emissions in twenty-four sub-Saharan African nations.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is however crucial to note that the scope of the latter study is smaller compared to Ben Jebli et al ( 2015 ) since they only examined the specific case of the Nigerian economy among other sub-Saharan African states. Other studies on Africa like Nwani et al ( 2021 ) for the case of the Algerian economy have also bypassed the examination of the EKC. Therefore, the growing debate on the validity of the hypothesis is still open to further investigation.…”
Section: Literature Reviewmentioning
confidence: 99%